Tailoring the immune response to wheat gliadin by enzymatic transamidation. (May 2019) - Luongo, Diomira; Bonavita, Roberta; Rossi, Stefano; Rotondi Aufiero, Vera; Feliciello, Nicoletta Rosaria; Maurano, Francesco; Iaquinto, Gaetano; Mazzarella, Giuseppe; Rossi, Mauro
Highlights: Transamidated gliadin upregulates the IL-10 mRNA in CD intestinal biopsies. Transamidated gliadin increases the IL-10/IFN-γ ratio in CD intestinal biopsies. Transamidated gliadin stimulates an anti-inflammatory phenotype in HLA-DQ8 mice. This property is associated with specific α-gliadins. Abstract: Enzymatic transamidation of wheat gliadin by microbial transglutaminase inhibits IFN-γ secretion by intestinal T cell lines from celiac disease (CD) patients. Here, we analysed its effects on intestinal biopsies from CD patients and studied the underlying mechanisms in HLA-DQ8 transgenic (tg) mice, a model of T-cell mediated gluten sensitivity. In vitro challenge with a soluble form of transamidated gliadin (spf) upregulated IL-10 transcript levels in human biopsy samples. Furthermore, the ratio of IL-10/IFN-γ transcripts was significantly increased following treatment with spf. In DQ8 tg mice, recall responses in vitro in the presence of dendritic cells pulsed with transamidated gliadin showed that gliadin-specific CD4 + T cells did not produce IFN-γ at any tested dose. On the contrary, spf-specific CD4 + T cells still secreted IFN-γ, but they also produced significant levels of IL-10 with both native and transamidated gliadin. Interestingly, this anti-inflammatory activity was restricted to a specific reverse-phase high-pressure liquid chromatography (RP-HPLC) fraction encompassing α-gliadins. These findings suggested an ability of transamidated gliadin to revert, as well as to prevent, the inflammatory phenotype triggered by native gliadin. This property was intrinsically associated with specific components of the α-gliadin fraction.